The Avian Encephalomyelitis Virus (AEV) 5' Untranslated Region Contains an IRES with Similarity to the Hepatitis C Virus IRES - M Bakhshesh; L Roberts; G J Belsham (Tehran University of Medical Sciences, 2005)
Cap-independent internal initiation of protein synthesis has been shown to occur on a number of viral and cellular mRNAs. Initiation of protein synthesis is directed by an internal ribosome entry site (IRES) element within the 5' untranslated region (UTR) of the mRNA. Avian encephalomyelitis virus (AEV) belongs to the picornavirus family and shares protein sequence similarity with hepatitis A virus (HAV). Because of this, it was assigned to the hepatovirus genus. We have demonstrated that the 494 nucleotide 5' UTR of this virus genome contains an internal ribosome entry site (IRES) element. However, in contrast to the HAV IRES, the AEV IRES functions efficiently in the presence of cleaved eIF4G, suggesting functional differences exist. Furthermore, comparison of the AEV IRES sequence with that of the hepatitis C virus (HCV) IRES revealed areas of striking similarity, especially in the region of the ribosome binding site. The AEV IRES is thus very similar to the recently described IRES from the picornavirus porcine teschovirus; this IRES also shows similarity to the HCV IRES. These results suggest that these viruses may have exchanged sequences during evolution.